Adaptive Event-Triggered Control of Nonlinear Systems With Controller and Parameter Estimator Triggering - Huang, Jiangshuai; Wang, Wei; Wen, Changyun; Li, Guoqi (IEEE transactions on automatic control, 2020)
In this note, the event-triggered adaptive control for a class of uncertain nonlinear systems is considered. Unlike the traditional adaptive event-triggered control, the controller and parameter estimator are event-triggered simultaneously. Asymptotical convergence of stabilization error is guaranteed. To solve this problem, we design a set of event-triggering conditions, which is updated for each triggering. At the same time, the input-to-state stable assumption is not needed. It is shown that the proposed control schemes guarantee that all the closed-loop signals are globally bounded and the stabilization error converges to the origin asymptotically. Simulation results illustrate the effectiveness of our scheme.